Smart women and small business : - Wilmerding, Ginny (John Wiley & Sons, 2006)
The goal of this book is to get you started on the path to a successful career in the small business world, a world that needs experienced, smart, versatile women like you to join its ranks. Smart Women and Small Business is the ultimate professional guide for mid-career, business-minded women who want to achieve the same independence and success as their entrepreneurial male peers—but in their own way